Collaborative Governance and Creative Business of Local Craft Products in the New Adaptation Era in Bulukumba Regency (Case Study of Tanah Beru Kelurahan) - Syarial, Muh. Zainuddin Badollahi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to identify collaborative governance and creative business of local crafts in the New Normal era in Tanah Beru. This study uses a qualitative approach with data collection methods of observation, interviews and documentation. Based on the results of the study, it was found that in the new normal, MSME actors collaborated with the government which was manifested in the form of providing social assistance, reducing loan interest, training and seminars to increase the capacity of MSME actors, and encouraging UMKM actors to remain productive by producing international quality products.